Psychological Dynamics of Domestic Violence Victims: A Qualitative Study - Suriyati (Journal of Indonesian Scholars for Social Research, 2024)
This study aims to understand the psychological dynamics experienced by victims of domestic violence through a qualitative approach. By focusing on the subjective experiences of victims, this study explores how domestic violence affects the mental and emotional state of victims, as well as the coping strategies they use to survive. Data were obtained through in-depth interviews with a number of victims of domestic violence, which were then thematically analysed to identify common psychological patterns. The results showed that victims of domestic violence experience various forms of psychological trauma, including fear, depression, anxiety, and a sense of worthlessness. In addition, many victims also experience internal conflict between the desire to leave a harmful relationship and a sense of emotional or economic dependence on the perpetrator. The coping strategies used by victims vary, ranging from seeking social support to using defensive mechanisms such as denial and avoidance. This study highlights the complexity of the psychological experiences of victims of domestic violence and the need for intervention approaches that are more holistic and sensitive to the psychological needs of victims. The results of this study are expected to contribute to the development of more effective policies and services in supporting the recovery of victims of domestic violence.